Purification and characterization of the exopolygalacturonase produced by Aspergillus giganteus in submerged cultures - Pedrolli, Danielle Biscaro [UNESP]; Carmona, Eleonora Cano [UNESP] (Springer Heidelberg, 2010)
Polygalacturonases are pectinolytic enzymes that catalyze the hydrolysis of the plant cell-wall pectin backbone. They are widely used in the food industry for juice extraction and clarification. Aspergillus giganteus produces one polygalacturonase (PG) on liquid Vogel medium with citrus pectin as the only carbon source. In specific applications, such as those used in the food and medicine industries, the PG must be free of substances that could affect the characteristics of the product and the process, such as color, flavor, toxicity, and inhibitors. We present here an efficient, simple, and inexpensive method for purifying the A. giganteus PG and describe the characteristics of the purified enzyme. Purified PG was obtained after two simple steps: (1) protein precipitation with 70% ammonium sulfate saturation and (2) anion-exchange chromatography on a DEAE-Sephadex A-50 column. The final enzyme solution retained 86.4% of its initial PG activity. The purified PG had a molecular weight of 69.7 kDa, exhibited maximal activity at pH 6.0 and 55-60A degrees C, and was stable in neutral and alkaline media. It had a half-life of 115, 18, and 6 min at 40, 50 and 55A degrees C, respectively. Purified PG showed its highest hydrolytic activity with low-esterified and nonesterified substrates, releasing monogalacturonic acid from substrate, indicating that it is an exopolygalacturonase. PG activity was enhanced in the presence of beta-mercaptoethanol, dithiothreitol, Co(2+), Mn(2+), Mg(2+), NH(4) (+), and Na(+) and was resistant to inhibition by Pb(2+).
Keywords: Aspergillus giganteus; Enzyme characterization; Enzyme purification; Exopolygalacturonase; Pectinase